Effect of inoculum size and agitation speed on bioethanol production by Kluyveromyces marxianus using sugarcane molasse - Vitta Rizky Permatasari; Amilatun Mardiyah; Suprayogi Suprayogi; Nur Hidayat (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
In this study, bioethanol production was carried out at a high temperature (40 0C) using Kluyveromyces marxianus in sugar cane molasses media with a study of combinations in fermentation conditions in the form of inoculum concentration and agitation speed. This study investigated the effect of inoculum concentration and agitation speed on bioethanol production. This study used a factorial randomized block design with two factors: inoculum concentration (with levels of 5%, 10%, and 15% (v/v)) and agitation speed (with levels of 100, 150, and 200 rpm). The results showed that the interaction of inoculum concentration and agitation speed significantly decreased pH, total sugar consumption, total reducing sugar Â (TRS) consumption, and total dissolved solids (TDS). However, an increase in cell optical density (OD), ethanol concentration, and ethanol yields was evident from all treatments. The best treatment was from a combination of 10% inoculum with an agitation speed of 150 rpm, giving the highest ethanol concentration of 3.44% and ethanol yields of 89.91%.